Pengaruh Struktur Kepemilikan dan Pengungkapan Sustainability Report Terhadap Nilai Perusahaan Sektor Properti, Real Estate, dan Konstruksi di Indonesia dan Singapura - Etti Ernita Sembiring; Hardiyanti Hardiyanti (Politeknik Caltex Riau, 2020)
The purpose of this study is to examine the effect of managerial ownership, institutional ownership and sustainability report disclosure on company value in Indonesia and Singapore. This research used legitimacy theory which explains that stakeholders want certainty that the company has carried out its operational activities based on the prevailing rules in the community. The disclosure of the sustainability report will give a positive impression to stakeholders so that it can influence company value. In addition, managerial and institutional ownership will also affect firm value because managerial ownership will create an alignment of interests between the principal and the agent and institutional ownership can increase supervision. The samples of this research are property, real estate and construction sector companies in Indonesia which are listed on the IDX (Indonesia) and on SGX (Singapore) and published a Sustainability Report in 2017. The analytical tool used is multiple regression analysis. The results show that only managerial ownership has a significant effect on company value in the property, real estate and construction sector in Indonesia and only the sustainability report disclosure variable has a significant effect on company value in Singapore. Key words: managerial ownership, institutional ownership, sustainability report disclosure, company value